Rhythmic variability, language, and style: A replication and extension of nPVI findings with the RISM dataset. Issue 3 (26th May 2020) - Vukovics, Katherine; Shanahan, Daniel
Abstract : The normalised pairwise variability index (nPVI), has been frequently used to measure the rhythmic variance between musical onsets. For example, researchers have proposed connections between the nationalities of composers and the nPVI values of their music and native language. One particular issue, however, lies in the notion of intended nationality – composers frequently wrote in national styles other than their own. This study employs the RISM-World dataset to both replicate previous findings relating the rhythmic variance of melodies to the nationalities of composers, and to examine intended nationality in the music of Mozart and Handel, namely their operas and oratorios.